The Effects of Six Sigma Approach on Business Performance: A Study of White Goods (home appliances) Sector in Turkey - Erturk, Muzaffer; Tuerdi (Maimaitiali Tuerdi), Muhemmetali; Wujiabudula, Aihemaituoheti (ELSEVIER SCIENCE BV, 2016)
Increasing global competition in the world economy forces firms to sharpen their functionality and processes in order to gain competitive advantages. For this reason, many firms develop management systems. These methods provide interdisciplinary approaches including statistics and operational research which encompasses structure of the firm, market conditions, consumer needs and changes in economy and technology. These methods incorporate six sigma approach. The six sigma approach emerged in the 1980's. It provides important and better tools in comparing between firms in their pursuit to achieve their targets in the face of other competitors. In this context, the main aim of the study is to investigate the main structure of the six sigma approach and its characteristics and to analyze the effects of six sigma approach on the firm's performance indicators by considering a firm benefiting efficiently from six sigma approach and operating in the white goods sector in Turkey. (C) 2016 Published by Elsevier Ltd.
Keywords: Six Sigma; Technology and Innovation Development; Firm performance; Business & Economics